Analysis of Distance Learning During the Covid-19 Pandemic on Biology Learning at Senior High School of Bogor Regency - Widiastuti, Lina; Kurniasih, Surti; Prasetyorini, Prasetyorini (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2022)
This study aims to analyze the implementation of Distance Learning (PJJ) in biology learning in high school including implementation, obstacles, and results. The method used in this research is descriptive method. The population includes all high school students in the Bogor Regency area for the 2020/2021 academic year and biology teachers in the Bogor Regency area with a sample of 337 students from 10 schools and 60 biology subject teachers. This research data collection technique uses a questionnaire or a questionnaire via google form which is analyzed by describing various research results in the form of percentages. Based on the results of the study, it can be concluded that the implementation of PJJ has been going well. The indicators are the completeness of supporting facilities and infrastructure for PJJ, teacher readiness in implementing PJJ, student participation, student attendance rate, application and learning methods used, achievement of learning objectives, and completeness of student learning outcomes cognitively. Based on these indicators, 70% of students and 55% of teachers think that the implementation of PJJ has been running effectively. Obstacles faced in the implementation of PJJ include the lack of active students in learning, discipline in collecting assignments, poor internet network, lack of internet quota availability, difficulty understanding some materials and too many tasks that must be done by students.